Two essays on the universal and particular dimensions of culture - Pauw, J. C. (Jacobus Christoff) (Stellenbosch : Stellenbosch University, 2012)
The first of the two essays was presented at the conference 'Ethnicity in an Age of Globalisation', held at Uganda Martyrs University, Kampala, Uganda, from 3-6 September 2001.